2021
DOI: 10.1111/jopy.12662
|View full text |Cite
|
Sign up to set email alerts
|

Are social desirability scales desirable? A meta‐analytic test of the validity of social desirability scales in the context of prosocial behavior

Abstract: Socially desirable responding (SDR)-the tendency to present oneself overly positive and downplay negative attributes-has frequently been discussed as an issue hampering the validity and interpretation of self-reports (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 118 publications
1
14
0
Order By: Relevance
“…However, we did not find any evidence for this proposition in the present studies. Fur ther, the link between social desirability and prosocial behavior was more substantial and more consistent in the current studies than the effects reported in a recent meta-analysis (Lanz et al, 2022), suggesting that the employed measures assessed socially desirable traits (and not social desirability bias) as discussed by Lanz and colleagues (2022). On the other hand, we did not find a statistically significant correlation between social desirability and crying proneness (Supplementary Table 10).…”
Section: Crying Proneness and Moral Judgments And Behaviorsupporting
confidence: 85%
“…However, we did not find any evidence for this proposition in the present studies. Fur ther, the link between social desirability and prosocial behavior was more substantial and more consistent in the current studies than the effects reported in a recent meta-analysis (Lanz et al, 2022), suggesting that the employed measures assessed socially desirable traits (and not social desirability bias) as discussed by Lanz and colleagues (2022). On the other hand, we did not find a statistically significant correlation between social desirability and crying proneness (Supplementary Table 10).…”
Section: Crying Proneness and Moral Judgments And Behaviorsupporting
confidence: 85%
“…We were unable to consider faking indices for self-reports because such validated indices are missing. Lie scales have come under heavy criticism (e.g., De Vries et al, 2014 ; Lanz et al, 2021 ; Uziel, 2010 ), and even the scale’s authors strongly advise against the use of lie scales to detect faking (e.g., Borkenau & Ostendorf, 2008 ). Faking indices for IATs were created on the basis of recommendations from prior research (see Agosta et al, 2011 ; Cvencek et al, 2010 ; Röhner et al, 2013 ; Röhner & Thoss, 2018 ).…”
Section: Analytic Strategymentioning
confidence: 99%
“…From ancient times, Chinese society has expected teachers to be proactive and to go out of their way to help students. According to the social desirability theory, excellent interpersonal desirability will promote individuals’ careers to shape the corresponding self-belief and self-requirement ( Carlo et al, 1991 ; Braun et al, 2001 ; Lalwani et al, 2006 ; Wanat et al, 2020 ; Lanz et al, 2022 ). Consequently, the expectation of Chinese society that teachers should actively assist students will motivate teachers to meet and maintain this social expectation throughout their academic and professional careers ( Xuan, 2006 ; Li, 2017 ).…”
Section: Discussionmentioning
confidence: 99%